Robotics safety issues for human welfare in an automated manufacturing system - Bhuvenesh, Rajamony, Dr.; Mohamed Rizon, Mohamed Juhari, Dr. (Oita University, 2009)
Organized by Oita University, 23rd - 25th January 2006 at B-Con Plaza, Oita, Japan.